2011
DOI: 10.1007/s00101-011-1941-9
|View full text |Cite
|
Sign up to set email alerts
|

Kardioprotektion durch thorakale Periduralanästhesie?

Abstract: The present meta-analysis did not prove any positive influence of thoracic EDA on perioperative in-hospital mortality in patients undergoing noncardiac surgery. Furthermore, it remains questionable if thoracic EDA has the potential to reduce the rate of perioperative myocardial infarction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 72 publications
(54 reference statements)
0
8
0
Order By: Relevance
“…SA patients had an increased incidence miction if a postoperative catheter is not used. Continuing urinary dysfunction may be the result of neurological damage (6). In the present study, patients under SA did not need additional anesthesia.…”
Section: Discussionmentioning
confidence: 57%
“…SA patients had an increased incidence miction if a postoperative catheter is not used. Continuing urinary dysfunction may be the result of neurological damage (6). In the present study, patients under SA did not need additional anesthesia.…”
Section: Discussionmentioning
confidence: 57%
“…However, we have shown no difference in the evaluation of serum CK-MB, troponin values or ST segment analysis in a period of 24 hours postoperatively. In a recent meta-analysis including 2,758 patients and nine studies, it was demonstrated that TEA did not reduce perioperative myocardial ischemia or mortality in patients undergoing noncardiac operations [9]. However, there are limited data on perioperative outcome comparisons of patients undergoing thoracotomy procedure who had either a lumbar or thoracic epidural for postoperative pain management.…”
Section: Discussionmentioning
confidence: 99%
“…Only weak evidence exists that EDA is able to decrease postoperative cardiovascular and pulmonary complications for subgroups with major open vascular surgery or high-risk patients [ 23 , 27 ]. A 2011 meta-analysis investigating the effects of thoracic EDA on perioperative outcome failed to show a benefit on perioperative in-hospital mortality in noncardiac surgery [ 7 ]. In a single-center RCT, the preemptive use of EDA in patients undergoing open colon resection offered no advantage over IV-PCA with regard to the length of the hospital stay, pain scores, quality of life, complications, or hospital costs [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Major abdominal surgery frequently entails large volume shifts and significant blood losses. Some evidence exists that EDA provokes hemodynamic instability in this setting [ 6 , 7 ]. Typically, vasopressors and large amounts of fluids are administered to counteract undesirable hypotension.…”
Section: Introductionmentioning
confidence: 99%